Marine resource abundance drove pre-agricultural population increase in Stone Age Scandinavia - J. P. Lewis (Nature Portfolio, 2020)
How the development of human societies is influenced through their ecological environment and climatic conditions has been the subject of intensive debate. Here, the authors present multi-proxy data from southern Scandinavia which suggests that pre-agricultural population growth there was likely influenced by enhanced marine production.